Rehabilitation of acromioclavicular joint separations: Operative and nonoperative considerations - Cote, M. P.; Wojcik, K. E.; Gomlinski, G.; Mazzocca, A. D. (Clinics in Sports Medicine, 2010)
Acromioclavicular joint (AC) separations are one of the most common injuries seen in orthopedic and sports medicine practices, accounting for 9% of all injuries to the shoulder girdle. Various operative and nonoperative treatment schemes have been described for the management of AC joint injuries. Although there is controversy about the efficacy of surgical reconstruction versus nonoperative intervention for grade III type injuries, grade I and II separations seem to respond favorably to conservative management. Conversely, grades IV, V, and VI often require surgical reconstruction. Regardless of the type of injury, rehabilitation as a part of conservative management and postoperative care plays an important role in the management of these injuries. This article presents a rehabilitation approach to treatment of acromioclavicular separations pre- and postoperatively.